The Influence Of Celebrity Endorser, Brand Image And Word of Mouth on Purchase Decision - Ruth Natalina, Agung Kresnamurti Rivai, Andi Muhammad Sahdat (Islamic Education Journal, 2023)
The aims of this study to analyze the significant effect of celebrity endorser on word of mouth, to analyze the significant effect of brand image on word of mouth, to analyze the significant effect of celebrity endorser on brand image, to analyze the significant effect of celebrity endorser on purchase decision, to analyze the significant effect of brand image on purchase decision, to analyze the significant effect of word of mouth on purchase decision. to analyze the significant effect of celebrity endorser and word of mouth on purchase decision, to analyze the significant effect of brand image and word of mouth on purchase decision, to analyse the significant effect of celebrity endorser, brand image and word of mouth on purchase decision. The data collection in this study was by distributing questionnaires to 200 customer respondents in DKI Jakarta using MS Glow. In analyzing the research data, the Structural Equation Model (SEM) approach was used with the Lisrel application version 8.8. The results of this study are there is a positive and significant effect on e-satisfaction on electronic word of mouth, there is a positive and significant influence on e-trust on electronic word of mouth, there is a positive and significant influence on electronic word of mouth on repurchase intention, there is a positive influence and significant on e-satisfaction on repurchase intention, there is a positive and significant effect on e-trust on repurchase intention, there is a positive and significant effect on e-satisfaction on repurchase intention through electronic word of mouth, there is a positive and significant effect on e-trust on repurchase intentions through electronic word of mouth.